Analisis Korelasi Curah Hujan dan Lahan Terbangun Terhadap Luasan Genangan Banjir di Kabupaten Demak - Mikael Arvito Kurnia Adi; Agusta Praba Ristadi Pinem; Nurtriana Hidayati (Jurnal Informatika: Jurnal Pengembangan IT, 2026)
Demak Regency is a low-lying coastal area that faces two types of pressures due to natural phenomena and massive human activities. The purpose of this study is to examine changes in built-up land and measure the level of spatial relationship between rainfall and built-up land area with flood inundation area in Demak Regency during the period 2020 to 2024. The method used in this study is spatial quantitative based on cloud computing using the Google Earth Engine platform that utilizes CHIRPS data for rainfall, Dynamic World for built-up land, and Sentinel-1 for flood inundation area. The findings of this study indicate that the annual rainfall trend has a low level of correlation with a coefficient of determination ranging from 1% to 7% while changes in built-up land show a high level of correlation with a Pearson correlation value between -0.52 to -0.58 which indicate that the reduction of non-built-up land due to land conversion is directly propotional  to the expansion of inundation which contributes to the variation of flood inundation by around 34%. The increase in flood inundation area reaching ±6,970 Ha in 2024 amid normal rainfall confirms that the decline in environmental capacity occurs due to excessive land conversion. This study concludes that managing the risk of increased flooding in Demak Regency requires strict integration of spatial planning policies, not just relying on a meteorology-based early warning system.